Fugitives - Smith, Alexander Gordon, 1979- (New York : Farrar Straus Giroux, 2012)
After achieving the impossible by escaping the laboratories and cells of Furnace Penitentiary, Alex, injected with superhuman abilities, must uncover the last of Furnace's secrets--the truth about the man who built the prison.
Originally published: Great Britain : Faber and Faber, 2010.
950
Keywords: Prisons -- Juvenile fiction; Fugitives from justice -- Juvenile fiction; False imprisonment -- Juvenile fiction; Science fiction